RadioAstron orbit determination and evaluation of its results using correlation of space-VLBI observations. Issue 2 (15th January 2020) - Zakhvatkin, M.V.; Andrianov, A.S.; Avdeev, V.Yu.; Kostenko, V.I.; Kovalev, Y.Y.; Likhachev, S.F.; Litovchenko, I.D.; Litvinov, D.A.; Rudnitskiy, A.G.; Shchurov, M.A.; Sokolovsky, K.V.; Stepanyants, V.A.; et al.
Abstract: A crucial part of a space mission for very-long baseline interferometery (VLBI), which is the technique capable of providing the highest resolution images in astronomy, is orbit determination of the mission's space radio telescope(s). In order to successfully detect interference fringes that result from correlation of the signals recorded by a ground-based and a space-borne radio telescope, the propagation delays experienced in the near-Earth space by radio waves emitted by the source and the relativity effects on each telescope's clock need to be evaluated, which requires accurate knowledge of position and velocity of the space radio telescope. In this paper we describe our approach to orbit determination (OD) of the RadioAstron spacecraft of the RadioAstron space-VLBI mission. Determining RadioAstron's orbit is complicated due to several factors: strong solar radiation pressure, a highly eccentric orbit, and frequent orbit perturbations caused by the attitude control system. We show that in order to maintain the OD accuracy required for processing space-VLBI observations at cm-wavelengths it is required to take into account the additional data on thruster firings, reaction wheel rotation rates, and attitude of the spacecraft. We also investigate into using the unique orbit data available only for a space-VLBI spacecraft, i.e. the residual delays and delay rates that result from VLBI data processing, as a means to evaluate the achieved OD accuracy. We present the results of the first experience of OD accuracy evaluation of this kind, using more than 5000 residual values obtained as a result of space-VLBI observations performed over 7 years of the RadioAstron mission operations.